Nutritional, social, and environmental predictors of scholastic and psychosocial outcomes in school-going Indian adolescents: Findings from the UDAYA study (OR32-07-19) - Scott, Samuel P.; Nguyen, Phuong Hong; Pant, Anjali; Menon, Purnima (Oxford University Press, 2019)
Adolescent wellbeing is now recognized as critical to breaking the intergenerational cycle of poverty and malnutrition. Multiple factors shape cognitive wellbeing during adolescence, thus we sought to take a holistic approach in examining factors related to mental outcomes among Indian adolescents.